The Effect of Project-Based Learning With Liveworksheet for Improving Students’ Critical Thinking Skills - Putri, Nur Tasya; Emiliannur, Emiliannur; Sari, Silvi Yulia; Winarno, Nanang; Hakim, Lukman (Universitas Muhammadiyah Purworejo, 2026)
This study aims to check how the PjBL approach in the e-LKPD method improve students’ critical thingking skills at SMA N 1 Batang Kapas. The research used a one-group pretest-posttest design within a quasi-experimental framework. The population consisted of all Grade XI Phase F students at SMA N 1 Batang Kapas who took physics classes. The students’ were divided into two experimental groups, selected using purposive sampling, comprising two classes with 60 students in total. Data analysis used descriptive statistics including normality tests, t-tests with a significance threshold of 0.05. Research data was collected through essay tests administered in the form of pretests and posttests. Data analysis examined the KKTP scores, followed by the N-gain test, the normality test, and the hypothesis test. The analysis results showed that the KKTP comparison resulted in an increase in student learning outcomes of 93.33 percent. The n-gain test results of 0.69 and 0.64 were in the moderate category. The normality test results indicated that students' critical thinking skills were normally distributed. Based on the hypothesis test, there was a significant difference between the average pretest and posttest scores of students. Therefore, it can be concluded that the Project-Based Learning-Based e-LKPD is effective in improving students' critical thinking skills.